Targeted insertion of regulatory elements enables translational enhancement in rice - Shen, Rundong; Yao, Qi; Zhong, Dating; Zhang, Xuening; Li, Xinbo; Cao, Xuesong; Dong, Chao; Tian, Yifu; Zhu, Jian-Kang; Lu, Yuming (Frontiers in Plant Science, 2023)
In-locus editing of agronomically-important genes to optimize their spatiotemporal expression is becoming an important breeding approach. Compared to intensive studies on mRNA transcription, manipulating protein translation by genome editing has not been well exploited. Here, we found that precise knock-in of a regulating element into the 5’UTR of a target gene could efficiently increase its protein abundance in rice. We firstly screened a translational enhancer (AMVE) from alfalfa mosaic virus using protoplast-based luciferase assays with an 8.5-folds enhancement. Then the chemically modified donor of AMVE was synthesized and targeted inserted into the 5’UTRs of two genes (WRKY71 and SKC1) using CRISPR/Cas9. Following the in-locus AMVE knock-in, we observed up to a 2.8-fold increase in the amount of WRKY71 protein. Notably, editing of SKC1, a sodium transporter, significantly increased salt tolerance in T2 seedlings, indicating the expected regulation of AMVE knock-in. These data demonstrated the feasibility of such in-locus editing to enhance protein expression, providing a new approach to manipulating protein translation for crop breeding.